Constructing a cyclical Systemic Risk Indicator (cSRI) for Malta - Sarah Vella (Central Bank of Malta, 2024)
Cyclical systemic risk arises when macro-financial imbalances accumulate over time. Past financial crises which occurred in several countries around the world have shown that heightened cyclical risk can lead to exorbitant economic and financial costs if the appropriate macroprudential policies are not enacted at the correct time. Although many indicators are monitored in the conduct of macroprudential oversight and analysis, there is to date no in-house country-specific composite indicator for cyclical risk for Malta developed by the Central Bank of Malta. This paper addresses this gap by building a cyclical systemic risk indicator (cSRI). The cSRI is driven by the 2-year growth rate in real bank credit, the 1-year change in the debt service to income ratio, the house price to income ratio and the 2-year growth rate in real total debt. These sub-indicators are believed to have early warning characteristics on financial distress. This indicator forms part of a cyclical risk analysis framework of the Central Bank of Malta, complementing other tools that support the formulation of macroprudential policy recommendations.
Keywords: G21; G23; G51; 330; Cyclical systemic risk; Real bank credit; House price to income; Debt service to income; Real total debt